Executive Functions and Language: Their Differential Influence on Mono- vs. Multilingual Spelling in Primary School - Czapka, Sophia; Klassert, Annegret; Festman, Julia (Frontiers in Psychology, 2019)
We investigated the question of whether the same abilities predicted spelling performance in mono- versus multilingual primary school children. We focused on executive functions (EF) and language-related skills, in particular lexicon size and phonological awareness, because multilingualism can modulate these factors: There is evidence for (a) a bilingual advantage in EF due to constant high cognitive demands through language control, (b) a smaller mental lexicon and (c) possibly better phonological awareness. Multilinguals in Germany show on average inferior German language proficiency, what can influence performance in language-based tasks negatively. Thus, we included two spelling tasks to tease apart spelling based on lexical knowledge (i.e., word spelling) from spelling based on non-lexical strategies (i.e., nonword spelling). Our sample consisted of two heterogeneous groups from third grade classes in Germany: 69 monolinguals (age: M = 107.6 months) and 57 multilinguals (age: M =111.0 months). Compared to monolinguals, multilinguals performed significantly more poorly on tasks measuring German lexicon size, German language proficiency and word spelling. However, on less language-dependent tasks (e.g., nonword spelling, phonological awareness, intelligence, short-term memory and the three EF components, namely switching, inhibition and working memory) their performance did not differ significantly from their monolingual peers. Regression analyses revealed that EF influenced only monolinguals’ spelling performance: Switching predicted both word and nonword spelling and inhibition influenced word spelling. No influence of working memory was found. However, by adding lexicon size and other language-related factors to the regression models, the influence of EF on monolinguals was reduced to marginal effects in word spelling and nonsignificant effects in nonword spelling. In terms of language-related skills, phonological awareness influenced both language groups, but multilinguals’ word spelling performance was also predicted by their German lexicon size. For multilinguals, only language-related predictors explained variance in their spelling performance. This study offers an in-depth look at spelling acquisition at a certain point of literacy development. For German multilingual third graders, language knowledge was more important than EF, which might come into play only at a later stage. Probably due to superior language knowledge, their monolingual peers were already able to make use of EF during spelling.